Safety of pregnancy in uterine fibroids - Alhainiah, Maha; Aljifry, Elaf; Alghamdi, Ayman; Alrabghi, Lujain; Alharbi, Abdullah; Alrowaithi, Ezdehar; Almuallem, Fatimah; Fakeih, Elaf; Alrowaithi, Bassmah; Allam, Hassan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Uterine fibroid is one of the most common intrauterine masses among females at the reproductive age. Pregnancy and uterine fibroids are highly correlated. Pregnancy-related hormones influence the size of uterine fibroids, and fibroids have many impacts on pregnancy. Although most if the uterine fibroids are asymptomatic during pregnancy, serious complications may occur. The main complications include abortion, premature rupture of membranes, premature labor, abruptio placentae, peripartum hemorrhage, fetal malpresentation, fetal intrauterine growth retardation, small for gestational age infants, and fetal anomalies. The main risk factors for complications are related to the fibroid number, size, volume, location, and type. Large, multiple, retroplacental, submucosal, subserosal, pedunculated, or low-lying fibroids carries the highest risk for complications during pregnancy. This review will address the prevalence of uterine fibroids during pregnancy, its effects, and complications.